2005
DOI: 10.1007/s10750-005-4286-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biotic and Abiotic Factors on Psammic Rotifers in Artificial and Natural Lakes

Abstract: The effect of sand grain size, porosity and the abundance of algae on the community structure of psammic rotifers was tested in three anthropogenic lakes (Upper Silesia) and compared with three natural ones (West Pomerania). The structure of grain size in the studied beaches of artificial and natural lakes was similar but differences were found in the abundance of algae. The structure of the psammic rotifer community in Upper Silesian lakes was different from natural lakes in West Pomerania. The structure of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…This is consistent with the study carried out on the Polish lakes with different trophic conditions, where higher values of the Shannon index and larger numbers of rotifer species were found in lakes with lower trophic status (Bielańska-Grajner 2005). This result supports the theory that the trophic status of a water body affects the diversity of zoopsammon communities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the study carried out on the Polish lakes with different trophic conditions, where higher values of the Shannon index and larger numbers of rotifer species were found in lakes with lower trophic status (Bielańska-Grajner 2005). This result supports the theory that the trophic status of a water body affects the diversity of zoopsammon communities.…”
Section: Discussionsupporting
confidence: 92%
“…Ejsmont-Karabin (2004) also reported that bdelloids prefer the finest grain fraction. There are studies, however, where no significant correlations were found between the number of rotifers and the sand grain size (Bielańska-Grajner 2005). Being fine and small particle feeders, bdelloids should favor higher quantities of plant debris and associated bacteria in the arenal of L. Võrtsjärv.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, dominant ciliates, nematodes, and bdelloids were generally not identified to lower taxa, which may further bias the overall pattern of diversity. However, a similar relationship between the number of rotifer species and trophic state was found in a study carried out in Poland, where more rotifer species were found in lakes with a lower trophic status (Bielańska-Grajner, 2005). In another study in the same ecoregion the species richness was notably lower in hypertrophic lakes (Ejsmont-Karabin, 2003).…”
Section: Resultssupporting
confidence: 78%
“…The maximum density of rotifers in Lake 111 sediments was always <25 individuals cm −3 . Although methodological constraints render comparisons with other systems difficult, it appears that adult rotifer densities were similar to, or lower than, densities observed in oligotrophic Lake Brunnsee, Germany (mean = 33 individuals cm −3 ; Bergtold & Traunspurger 2004) and in Silesian lakes in Poland (<17 individuals cm −3 ; Bielanska‐Grajner 2005). The egg densities in Lake 111 were extremely low compared to the values compiled by Hairston (1996; see his table 1, p. 1088) and other studies (e.g.…”
Section: Discussionmentioning
confidence: 77%